KEADILAN SAHABAT (Telaah Historis dalam Perspektif Metodologis) - Tangngareng, Tasmin (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2019)
This article examines the equitableness of the Prophet’s companion (‘adalah al-sahabah) through historical and methodological perspective. The term of ‘adl means ‘straight’, ‘balance’, ‘impartial’ or ‘put something on the right place’. In the Hadith perspective, ‘adl (equitably) is a man who constantly commands the right and forbids the wrong. Thus, its clear that ‘adl is a nature or a character of somebody which lead him to the right action. The term of ‘sahabah’ rooted from sa-hi-ba means ‘owner’ or ‘accompany’. In Hadith perspective, sahabah is a man who had been living along with The Prophet Muhammad for a or several years or involved once or several times in a war together with The Prophet Muhammad. Sahabah also means a man who met The Prophet Muhammad in the belief circumstances. Majority of ulamas (muslim scholar) said that the ‘adalah al-sahabah is guaranteed, so that they do not have to be criticized. However, the debate of ‘adalah al-sahabah among ulamas can be deal with redefinition of ‘adl as this article aims.